2005
DOI: 10.1373/clinchem.2005.055442
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Urinary Orosomucoid in Acute Inflammation: Observations on Urinary Excretion of Orosomucoid, Albumin, α1-Microglobulin, and IgG

Abstract: Background: Inflammation-associated proteinuria in acute, nonrenal disease is a common but poorly understood phenomenon. We performed an observational study of the urinary excretion of orosomucoid (␣ 1 -acid glycoprotein), albumin, ␣ 1 -microglobulin (protein HC), and IgG to obtain quantitative and temporal data on these 4 proteins. Methods: Urine samples were collected at daily intervals for up to 23 days from 6 patients with surgeryinduced inflammation and at hourly intervals for a 24-h period from 7 sepsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
2
14
0
3
Order By: Relevance
“…The aggregate concentration in plasma of globulins with a molecular size similar to albumin, proteins such as transferrin, ␣ 1 -acid glycoprotein, ␣ 1 -proteinase inhibitor, ␣ 1 -antichymotrypsin, ␣ 2 -HS glycoprotein, hemopexin, Gc-globulin, and many others (31 ), in healthy individuals is ϳ25% that of albumin; this aggregate concentration is even higher during acutephase reactions (32 ). Because the passage of plasma proteins through the glomerular barrier into urine is primarily a size-dependent process with a size-exclusion limit approximately the size of albumin (33 ), it is not surprising that all of the albumin-sized plasma components are also found in urine (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(33)(34)(35)(36)(37)(38)(39). There is considerable variation in the reported proportions of individual globulins relative to albumin in urine (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aggregate concentration in plasma of globulins with a molecular size similar to albumin, proteins such as transferrin, ␣ 1 -acid glycoprotein, ␣ 1 -proteinase inhibitor, ␣ 1 -antichymotrypsin, ␣ 2 -HS glycoprotein, hemopexin, Gc-globulin, and many others (31 ), in healthy individuals is ϳ25% that of albumin; this aggregate concentration is even higher during acutephase reactions (32 ). Because the passage of plasma proteins through the glomerular barrier into urine is primarily a size-dependent process with a size-exclusion limit approximately the size of albumin (33 ), it is not surprising that all of the albumin-sized plasma components are also found in urine (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(33)(34)(35)(36)(37)(38)(39). There is considerable variation in the reported proportions of individual globulins relative to albumin in urine (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…During acute-phase responses, for example, the urinary concentration of ␣ 1 -acid glycoprotein reaches ϳ80% that of albumin (24 ). A second problem with the size-exclusion HPLC analysis is that several urinary components, although not exactly coeluting with albumin, overlap considerably.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously we showed that u-ORM could be a more sensitive marker of inflammation than serum ORM which rises only 2-fold in contrast to even 200-fold increase of u-ORM in sepsis ( 21 ). Others also showed that the elevation of u-ORM is much more considerable than that of serum ORM in relation to inflammatory diseases ( 10 , 11 , 17 ). These results indicate that u-ORM is a reliable marker of chronic and acute inflammatory disorders and provides valuable supplementary information for daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%